Essential Role for the Legionella pneumophila Rep Helicase Homologue in Intracellular Infection of Mammalian Cells - Harb, Omar S. (American Society for Microbiology, 2000)
We have previously isolated 32 mutants of Legionella pneumophila that are defective in the infection of mammalian cells but not protozoa. The mutated loci have been designated macrophage-specific infectivity (mil) loci. In this study we characterized the mil mutant GK11. This mutant was incapable of growth within U937 macrophage-like cells and WI-26 alveolar epithelial cells. This defect in intracellular replication correlated with a defect in cytopathogenicity to these cells. Sequence analysis of the GK11 locus revealed it to be highly similar to rep helicase genes of other bacteria. Since helicase mutants of Escherichia coli are hypersensitive to thymine starvation, we examined the sensitivity of GK11 to thymineless death (TLD). In the absence of thymine and thymidine, mutant GK11 did not undergo TLD but was defective for in vitro growth, and the defect was partially restored when these compounds were added to the growth medium. In addition, supplementation with thymidine or thymine partially restored the ability of GK11 to grow within and kill U937 macrophage-like cells. The data suggested that the low levels of thymine or thymidine in the L. pneumophila phagosome contributed to the defect of GK11 within macrophages. Using confocal laser scanning microscopy, we determined the effect of the mutation in the Rep helicase homologue on the intracellular trafficking of GK11 within macrophages. In contrast to the wild-type strain, phagosomes harboring GK11 colocalized with several late endosomal/lysosomal markers, including LAMP-1, LAMP-2, and cathepsin D. In addition, only 50% of the GK11 phagosomes colocalized with the endoplasmic reticulum marker BiP 4 h postinfection. Colocalization of BiP with GK11 phagosomes was absent 6 h postinfection, while 90% of the wild-type phagosomes colocalized with this marker at both time points. We propose that the low level of thymine within the L. pneumophila phagosome in combination with simultaneous exposure to multiple stress stimuli results in deleterious mutations that cannot be repaired in the rep helicase homologue mutant, rendering it defective in intracellular replication.